EDUKASI TENTANG PENGGUNAAN MASKER DAN PENNGELOLAAN SAMPAH MASKER PADA IBU-IBU PKK RT 033, RW 09 KELURAHAN DEMANGAN, KECAMATAN GONDOKUSUMAN, YOGYAKARTA - Nur Apriliyanti; Septian Emma Dwi Jatmika (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
The corona virus (COVID-19) has become a worldwide case, one of the countries experiencing it is Indonesia. This COVID-19 caused many people to be infected and the impact of this outbreak caused economic losses. Indonesia The prevalence of COVID-19 in the Special Region of Yogyakarta City was confirmed at 16092 with the distribution of 68.15% of people being treated, 1.87% of people dying, and 29.98% of people recovering. The case of COVID-19 is still running and continues to increase accompanied by the prevalence rate of recovery but this is still a concern for the Yogyakarta City government, recorded 980 people being treated, 1879 people recovering, 92 people dying. This counseling aims to improve and change people's behavior in RT 033 in the use of masks and in the management of mask waste. There are still many people in RT 033 who have not implemented the use of masks and manage the mask waste themselves. The method used is divided into 3 stages, namely the planning stage there is program preparation, making media flyers and power points, and making observations in RT 033. The implementation stage includes counseling. The evaluation stage includes filling out the pre-test and post-test. Wilcoxon test results with a positive rank of 10, meaning that all participants in this counseling experienced a very significant increase in knowledge.